Kontribusi Relatif Lingkungan Sekolah Islami Dan Peran Teman Sebaya Terhadap Sikap Moderasi Beragama Siswa MI Muhammadiyah 1 Kota Probolinggo - Vidayanti, Vivit; Rifai, Mohammad Saiful; Andriani, Lusi (Educational Research Center, 2026)
This study aims to analyze the relative contribution between the Islamic school environment and the role of peers on students' religious moderation attitudes at MI Muhammadiyah 1 Probolinggo City. Using a quantitative approach with a multiple linear regression design, this study involved all sixth grade students as respondents. The results of the regression test showed that both variables had a significant effect on students' religious moderation attitudes. The Islamic school environment had a B coefficient of 0.510 (p < 0.001) and the role of peers had a B coefficient of 0.240 (p = 0.004). The F test showed that the overall regression model was significant with an F value of 55.657 (p < 0.001), while the R Square value of 0.547 indicated that this model could explain approximately 54.7% of the variation in religious moderation attitudes. These results confirm that the Islamic school environment and the role of peers significantly influence students' religious moderation attitudes. This research provides important insights for educational institutions to create an environment that supports the development of religious moderation attitudes by prioritizing the values ​​of tolerance and inclusivity in every aspect of school life.